Penegakan Hukum Pidana Terhadap Pelaku Tindak Pidana Pencemaran Dan Perusakan Lingkungan Hidup - Fitri Fitri (Universitas Palangka Raya, 2024)
Enforcing criminal law against perpetrators of environmental pollution and destruction crimes is crucial for environmental preservation. This article aims to examine the enforcement of criminal law against such offenders through a literature review method. Research findings indicate that despite existing laws and regulations on environmental protection, criminal law enforcement still faces various challenges. Lack of inter-agency coordination, limited human resources and budget, and low public awareness are hindering factors in criminal law enforcement. To enhance the effectiveness of criminal law enforcement, synergy and commitment from various parties are required. Institutional strengthening needs to be carried out by clarifying the duties, functions, and authorities of each agency in handling environmental crimes. Continuous capacity building of human resources is also necessary through specialized education and training. Efforts to increase public awareness and participation can be undertaken through campaigns, outreach, and environmental education. Furthermore, an evaluation and updating of regulations are needed to ensure deterrent effects for offenders and prevent the recurrence of environmental crimes in the future. Criminal sanctions imposed must be proportionate to the impact of the damage caused. With these efforts, it is hoped that criminal law enforcement can become an effective instrument in preserving the environment in Indonesia.